(3GdOQI GdfLajIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s
(3ChdgG (B:s
(3CaJJM GdebGd HYO GdHSedI HMeO NjQ eYfe hGdTcQ dg eUdjG Ydi GdfHj GdQMeI hBdg GdCWgGQ hCgd GdYUeI hHYO aGdYde Whjd Sdeg (B...s
(3BNQgG (B:s
.. (3hGNJjQ ddJhMjO aj GdfgGjI hQHeG CSfO ddQhGjI hde GLO ddSJQ hGdELeGQ fUGHgG HCfJ HGdNjGQ hGOY YbbjH GdaQV HGdeCKhQ ef GdOYGA GdehLR GdeTghQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\113s
(3GdPQjYI (B8 - 78 ( 408)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis